2021
DOI: 10.1002/adfm.202101872
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Oxides for Cathodic Electrocatalysis of Energy‐Related Gases: From O2 to CO2 and N2

Abstract: The oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO2RR), and nitrogen reduction reaction (NRR) are important cathodic reactions for renewable fuel production and energy conversion technologies. However, the sluggish kinetics of these reactions hinders the practical applications of the relevant technologies. Perovskite oxides, a promising family of catalysts with great flexibility in composition and structure engineering, exhibit versatility in electrocatalysis of these reactions. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 130 publications
0
16
0
Order By: Relevance
“…Complex perovskite structures have a rich history due to their amenability to compositional tuning and defect engineering. The ability to systematically tune the crystal structure of these materials provides the flexibility necessary to undertake extensive structure–property analyses to tailor the properties of these materials. This capability has undoubtedly played a role in establishing perovskites as a leading material in applications ranging from superconductivity , to electrocatalysis. ,, Advances in each of these fields requires well-controlled synthetic routes and considerations for the complexity of the medium in which the solids are utilized. Electrocatalytic reactions, for example, take place at an interface in a condensed phase medium.…”
Section: Introductionmentioning
confidence: 99%
“…Complex perovskite structures have a rich history due to their amenability to compositional tuning and defect engineering. The ability to systematically tune the crystal structure of these materials provides the flexibility necessary to undertake extensive structure–property analyses to tailor the properties of these materials. This capability has undoubtedly played a role in establishing perovskites as a leading material in applications ranging from superconductivity , to electrocatalysis. ,, Advances in each of these fields requires well-controlled synthetic routes and considerations for the complexity of the medium in which the solids are utilized. Electrocatalytic reactions, for example, take place at an interface in a condensed phase medium.…”
Section: Introductionmentioning
confidence: 99%
“…Among transition-metal oxides, perovskites with the formula of ABO 3 have emerged as promising candidates in electrocatalytic oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) due to their unique structure and fine-tuned compositions. However, few studies have been focused on the exploration of perovskites toward HER. Recently, alkaline hydrogen production is realized by constructing perovskite oxide-based nanocomposites. , Notably, catalysts prepared through the in situ exsolution method exhibit high activity and stability by virtue of the strong synergistic effect among different components. By treating precursor in the air or reducing atmosphere, the in situ as-formed new phase, such as metal, alloys, ,, oxides, ,, carbides, etc., can serve as active sites for HER. Islam et al reported a Sr 0.95 Co 0.7 Nb 0.1 Ni 0.2 O 3−δ perovskite decorated with exsolved Co–Ni bimetallic nanoparticles by annealing in 10% H 2 /N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy results illustrate that the proportion of V 5+ increases compared with that of pristine Ba 3 (VO 4 ) 2 , which leads to the partial oxidation of Co 3+ into Co 4+ on the surface of BVCO19. It is known that the B site of perovskite serves as an active site for HER. , The generation of more Co 4+ sites favors the release of H 2 . In addition, the high percentage of O 2 2– /O – implies that oxygen vacancies existed on the surface of BVCO19, which facilitates the adsorption and dissociation of water.…”
Section: Introductionmentioning
confidence: 99%
“…To date, platinum (Pt)-based catalysts are the benchmark electrocatalysts, but their large-scale application suffers from high cost, supply scarcity, and poor stability. [7][8][9] Hence, plenty of work has been done on exploring high-activity and cheap Pt-free electrocatalysts, including, for example, metal carbides, [10][11][12][13][14][15] oxides, [16][17][18][19][20] and nitrides. [21][22][23][24][25] Among such catalysts, FeÀ NÀ C materials exhibit the most outstanding intrinsic ORR activity in both alkaline and acid electrolytes.…”
Section: Introductionmentioning
confidence: 99%